Inovasi Kebijakan Program Kalimasada Melalui Jemput Bola Administrasi Kependudukan Di Kelurahan Wonorejo Rungkut - Ima Nur Rosyida; Yusuf Hariyoko (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
E-Government and Digital Governance serve as crucial foundations in the transformation of public services, leveraging information and communication technology. The primary focus is to provide easy and efficient access for the community. Through innovations such as the